The effects of globalization on firm's stock in the selected Asian countries - Sepideh Haghi; Sayed Mahdi Mostafavi; Mehdi Behname (Atlantic Review of Economics, 2015)
This study aims to survey the effects of economic globalization on the firm's stock that is measured by the index of the stock market by using panel data in selected countries in Asia (Iran, Saudi Arabia, India, China, Singapore, Malaysia, Indonesia, South Korea, Russia, Pakistan, Philippines, Sri Lanka) during 1997 - 2013. Unit root tests indicate that the variables are stationary on the level. The results of F-test, Breusch-Pagan and Hausman tests show that the unilateral fixed effects must be applied. The results show that the economic globalization significantly improves stock market index. Moreover the positive and significant effect on the firm's stock depend on political globalization and dummy variable, however the negative and significant effect is related to the growth rate of government expenditure, the exchange rate and the interaction effects of economy.
Keywords: F6; G3; C33; 330; globalization; firm's performance; economic globalization Index (KOF); stock market index; panel data